The KARAKTERISASI ENZIM Β-SIKLODEKSTRIN DARI ISOLAT LOKAL (BTS3A, BTS3-B DAN CK-2) PROVINSI JAMBI - Desi Sagita; Rahmadevi (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2021)
The β-cyclodextrin glucosyltransferase (β-CGTase) enzyme is an extracellular enzyme that converts starch to cyclodextrins. Cyclodextrins are widely used in the pharmaceutical industry, one of which is to increase solubility. This enzyme is produced by bacteria, especially the genus Bacillus sp. BTS3A, BTS3B and CK-2 isolates that produce CGTase enzymes have been isolated from the soil of cassava and potato plantations. The bacteria are fermented in liquid Horikoshi media, then centrifuged at 4 ° C and then concentrated by freeze dry. The enzyme was purified by the ammonium sulfate precipitation method up to 59.61% for BTS3A, 59.6% for BTS3B and 58.1% for CK-2. Then dialyzed using a cellophane membrane with cut off 14 KDa in phosphate buffer. The cyclization activity of crude enzymes was characterized by varying incubation times of 30, 60, 120 minutes and incubation temperatures of 30 ℃, 37 ℃, 55 ℃. CGTase cyclization activity was measured based on the decrease in phenolphthalein absorbance at a wavelength of 550 nm. The β-CGTase enzyme from the three isolates showed the optimum percentage reduction at 55°C for 30 minutes incubation